Effectiveness of a school-based anxiety prevention program for standard four and five primary school children in Jerantut, Pahang, Malaysia - Ab Ghaffar, Siti Fatimah (2018)
Background : About 10 to 20% of children and adolescents globally, had mental health problems. The global prevalence of anxiety in children was 6.5%. Children suffering from anxiety were found to have an increased risk of psychiatric disorders. If anxiety in children are left untreated, they can cause problems in adulthood resulting in significant social and economic burden for family, society and nation. In 2015, the prevalence of mental health problems among Malaysian children aged 5 to 15 were 12.1%. School offers an ideal place for an early intervention and anxiety prevention program delivered in school environment may be an effective way in minimizing common barriers to mental health services utilization among school children in clinical setting. Objective: The objective of this study was to develop, implement and evaluate the effectiveness of a school-based anxiety prevention program among standard four and five primary school children. Methodology: There are two phases of the study with phase one, an analytical crosssectional study, was carried out among 739 standard 4 and 5 primary school children from 11 randomly selected government primary schools in Jerantut, Pahang. A validated, pretested self-administered questionnaire was used to collect the data on children’s socio-demographic characteristic, anxiety status, emotion regulation, selfesteem, social, adaptive functioning and perfectionism level. Data were analysed by using multiple linear regression. In phase two, the school-based anxiety prevention program was developed based on the predictors of anxiety gathered from the cross-sectional study, and Information, Motivation and Behavioural Skills (IMB) model. The school-based program comprised of four sessions. A two-group parallel cluster randomized controlled trial of a single blinded study was conducted to evaluate the effectiveness of the program, with schools as the unit of allocation and individual participants as the unit of analysis. A total of 11 primary schools were enrolled, 5 were randomly assigned to intervention schools and 6 were randomly assigned to control schools. Children from intervention schools received school-based anxiety program while children from control schools received usual curriculum class (wait-list control group). The primary outcome was symptoms of anxiety at baseline, immediately post-intervention and 3 months postintervention which were assessed by the short version of Revised Child Anxiety and Depression Scale (RCADS 25), whereas, the secondary outcomes which were worry coping skills and self-esteem at baseline, immediately post intervention and 3 months post-intervention were measured by the Children Worry Management Scale (CWMS) and Rosenberg Self-Esteem Scale (RSES), respectively. Data were analysed by using generalised linear mixed model. The level of significance was set at alpha = 0.05. Subgroup analyses were performed for children with anxiety. The SPSS version 20 was used for the data analysis. This study was approved by Ethics Committee for Research Involving Human Subjects, Universiti Putra Malaysia. Results: The response rate of phase one was 94.7%. The results showed that the prevalence of anxiety among respondents was 6.1%. The predictors of anxiety were gender, worry regulation skill (p=0.001) and self-esteem (p=0.001). In phase two, the response rate was 89.6%. At baseline, there was no significant difference between intervention and wait-list control groups for anxiety score (p=0.156), worry coping skill score (p=0.174) and self-esteem score (p=0.089). The school-based anxiety prevention program was effective in reducing anxiety score for the whole sample (F (4, 1098) = 5.887, p = 0.001) and anxiety subgroup (F (4, 52) = 6.704, p = 0.001). However, it was not effective in improving worry coping skill score and self-esteem score. Conclusion: The school-based anxiety prevention program was effective in reducing anxiety score. These findings recommend that the school-based anxiety prevention program could be implemented in the local school setting by integrating it into the school curriculum.